2017
DOI: 10.1095/biolreprod.116.142828
|View full text |Cite
|
Sign up to set email alerts
|

DDX4-EGFP transgenic rat model for the study of germline development and spermatogenesis †

Abstract: Spermatogonial stem cells (SSC) are essential for spermatogenesis and male fertility. In addition, these adult tissue stem cells can be used as vehicles for germline modification in animal models and may have application for treating male infertility. To facilitate the investigation of SSCs and germ lineage development in rats, we generated a DEAD-box helicase 4 (DDX4) (VASA) promoter-enhanced green fluorescent protein (EGFP) reporter transgenic rat. Quantitative real-time polymerase chain reaction and immunof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…Rat is considered a better model (than mice) for understanding the regulation of testicular functions [ 36 ]. Due to larger body size and higher blood volume and litter size, rats are more favored for surgical, physiological and pharmacological experiments [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rat is considered a better model (than mice) for understanding the regulation of testicular functions [ 36 ]. Due to larger body size and higher blood volume and litter size, rats are more favored for surgical, physiological and pharmacological experiments [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Histological analysis to identify rat PGCs by morphology (Beaumont and Mandl, 1963), alkaline phosphatase activity (Kemper and Peters, 1987) and immunostaining of some representative markers (Encinas et al, 2012;Leitch et al, 2010;Northrup et al, 2011) have provided a rough timeline for rat germline development. In a recent report, to visualize gonadal to adult germ cells in vivo, Ddx4-EGFP transgenic rats were generated (Gassei et al, 2017). However, owing to the absence of Ddx4 expression in earlier PGCs, the specification and migration stages of rat PGCs have not yet been documented.…”
Section: Introductionmentioning
confidence: 99%
“…We identified nonbuffalo antibodies by immunofluorescence staining of juvenile buffalo testis tissues. DDX4 (VASA) is a member of the DEAD‐box family, and the results showed that GATA4‐positive Sertoli cells and Leydig cells were not immunolabeled with VASA; VASA can be utilized as a molecular marker of germ cells, which has been reported in several mammals, including humans, cattle, pigs, and goats (Gassei et al, 2017; J. Kim et al, 2015; Sada et al, 2012; Xu et al, 2021). NANOS2 is an RNA‐binding protein that is mostly expressed in A S and A pr spermatogonia, is required for the self‐renewal of SSCs and is generally considered a marker of SSCs; when NANOS2 was knocked out, many undifferentiated A‐type spermatogonial cells were lost; however, overexpression of NANOS2 resulted in strong accumulation of undifferentiated A‐type spermatogonial cells (Codino et al, 2021; Sada et al, 2012).…”
Section: Discussionmentioning
confidence: 96%